#sendwine: An Analysis of Motherhood, Alcohol Use and #winemom Culture on Instagram. (May 2021) - Harding, Kelly D; Whittingham, Lisa; McGannon, Kerry R
Popular culture has recently seen the emergence of the so-called comical wine mom persona, particularly on social media sites such as Instagram. Given the increasing use of alcohol amongst women and the emergence of alcohol as a tool for women and mothers to assert agency and gender equity, a critical analysis of wine mom culture warrants attention. Forty Instagram posts associated with the #winemom hashtag were selected using theoretical sampling and analysed using reflexive thematic analysis. The central objective was to use a postfeminist lens to critically explore how wine mom culture is part of the consumption, (re)production and (re)configuration of the ideologies of 'good' and 'bad' motherhood occurring in online gendered spaces. The findings demonstrated the ubiquity of wine mom culture and its contribution to normalized images and meanings of 'liberated motherhood' that may have problematic sociocultural and health implications related to women's alcohol consumption.